Human Sperm Bioassay for Reprotoxicity Testing in Embryo Culture Media: Some Practical Considerations in Reducing the Assay Time - Amjad Hossain; Subhash Aryal; Collin Osuampke; John Phelps (Advances in Urology)
Human sperm assay (HSA) is a preferred in house quality control and proficiency test (PT) practiced in fertility laboratories. HSA is performed over varying durations, apparently without following set criteria. To better understand the assay time required for reprotoxicity testing in embryo culture media, we compared American-Association-of-Bioanalysts-(AAB-) administered HSA data to our own assay performed using PT samples obtained from AAB. Participating laboratories were required to culture sperm for 48 hours to determine media acceptability. Conclusions drawn from 48- and 24-hour observations were the same, suggesting that HSA could identify reprotoxic media in less time than required by AAB. Our assay revealed that changes in motility grade in adulterated media are significantly different from those in control media. Furthermore, grade changes can be identified earlier than differences in motility loss between samples. Analyzing motility and motility quality together provides a method for establishing an optimal time for HSA.